Analisis Dampak Kebijakan Moneter Dan Kebijakan Fiskal Terhadap Inflasi Di Indonesia Tahun 2001-2021 - Galuh Pamujiningrum, Virginia; Soebagyo, Daryono (GEMA EKONOMI, 2023)
A state known as inflation happens when there is a continual, unjustifiable increase or drop in the price of products. This condition has an effect on the economy. The goal of this study is to evaluate the factors that affected Indonesian inflation from 2001 and 2021. Quantitative data from secondary data sources are used in this investigation. Time series regression analysis with model parameter estimation utilizing the traditional assumption test, model goodness-of-fit test, and effect validity test is the analytical approach employed in this work. This study discovered that the BIRATE variable, compared to other factors in this model, such as the money supply, exchange rates, and budget deficits, had a positive and substantial impact on inflation in Indonesia over the period of 2001–2021